Analyzing English Politeness Main Character Thank You, Sorry, Please in “Hati Suhita” By Khilma Anis - Andayani, Tri; Siti Asyah; Sulistyaningsih, Sulistyaningsih; Wahyuni, Farida Eka (ITScience (Information Technology and Science), 2024)
The purpose of this study is to describe the analysis of English politeness main character: thank you, sorry, and please in the novel